Using Information Gap Activity to Increase Students' speaking Skill at the Twelve Grade of MAN 1 Pamekasan - Fuqaha, Ansharul; Ghofur, Abd (OKARA: Jurnal Bahasa dan Sastra, 2015)
Based on the researchers’ observation on the preliminary study on the teaching of speaking, the problem was found that the students’ speaking skill in the teaching and learning was very low. It was because the class was heterogeneous and the teacher used monotonous teaching activity. To cope of this problem, the researcher employed the Information gap activity. This study tries to prove how the Information-gap activity can increase students’ speaking skill at the third grade of MAN 1 Pamekasan. The study was design to increase the students’ speaking skill by using Information gap activity at MAN 1 Pamekasan. The study was collaborative classroom action research in which the researcher and the collaborator worked together, the researcher acted as the teacher while the collaborator observed the students during the implementation of the strategy. This study was conducted in one cycle consisting of six meetings using the following procedures; planning, implementing, observing and reflecting. The data of the study were collected through the observation checklists, field notes, and questionnaires. The subject of the study were 41 students of third grade on science 3 program MAN 1 Pamekasan.